Erythema migrans multiloculare in Styria (Austria) - Müllegger, R... R. (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1996)
To characterize clinical, serologica, and histopathologic features of patients with erythema migrans multiloculare from Styria (Austria), an European area well known to be endemic for Lyme Borreliosis, 270 consecutive patients (m:f = 128:142, mean age = 54 years) with erythema migrans were studied at the Department of Dermatology in Graz, Austria between March 1993 and October 1995. 17/270 patients (m:f = 9:8, mean age = 37 years) (6.3%) presented with a multifocal form ofo the disease. Several findings in these 17 patients were remarkable. Anamnestic data/clinical findings: History of tick or insect bite(s): 10/17 patients (4 singular, 6 multiple); mean total number of lesions/patient = 4 (ranging 2-18); latency of 1 - 14 days (mean 7 days) in 9/17 patients (53%) between primary erythema migrans and secondary lesions; in these 9 patients the secondary leioons showed a different morphologic aspect in comparison to the primary erythema migrans; extracultaneous signs and symptoms: 7/17 patients (41%). Serologic findings: Borrelia burgdorferi serum ELISA IgG-antibodies: 9/17 patients (53%), IgM: 9/17 patients (53%). Histopathologic findings: Complete lack of epidermal changes and milder inflammatory dermal infiltrate in all secondary lesions (4 biopsy specimens) in comparison to primary erythemata migrantia (5 biopsy specimens). Our clinical and serologica findings are lergely in accordance with the scarce literature on this condition from Europe where erythema migrans multiloculare is much rarer than in the . The pathogenesis of erythema migrans multiloculare which is currently defined to be a disseminated form of Lyme Borreliosis due to haematogenous spread of Borrelia burgdorferi will be discussed in consideration of our observations.
Keywords: Adult; Austria; Diagnosis; Epidemiology; Erythema; Etiology; Lyme disease; Middle age; Retrospective studies